Presentation: Genre: Diversity and Harmony - Caram Padilla, María José (2001)
Gender is a relatively new concept in our midst. It is not, as has often been understood, a feminine issue, although historically its genesis has had much to do with the irruption of women in social life and with their claims. It is much more than that, since it affects and involves all people, whether men or women, young or old. Nor is it just a cognitive tool, because, as Diego Irarrázaval says in his article, published in this magazine, "it is about a perspective and action that transforms human relationships and historical forms."